1976
DOI: 10.1136/bjo.60.12.816
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of xenon arc photocoagulation for central retinal vein occlusion.

Abstract: Twenty patients with central retinal vein occlusion were randomly divided into two groups in a prospective study to evaluate the effects of xenon are photocoagulation in central retinal vein occlusion. The patients in one group were treated with 360 degrees scatter xenon photocoagulation and the others received no treatment. The average follow-up was 18 months. There were no cases of rubeosis or neovascular glaucoma in the treated group. Two patients in the untreated group developed rubeosis with subsequent ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Results of this study are in accordance with the preliminary results reported by May et al (1976). In their randomised study on 20 eyes (10 treated, 10 untreated) 2 cases of neovascular glaucoma were found in the untreated group and none in the treated group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results of this study are in accordance with the preliminary results reported by May et al (1976). In their randomised study on 20 eyes (10 treated, 10 untreated) 2 cases of neovascular glaucoma were found in the untreated group and none in the treated group.…”
Section: Discussionsupporting
confidence: 92%
“…No significant improvement in visual acuity in spite of drying out of the macular oedema was found either by Theodossiadis (1976) or May et al (1976).…”
Section: Discussionmentioning
confidence: 77%
“…These findings have been confirmed120 and others have used panretinal photocoagulation to reverse neovascular glaucoma and rubeosis 9899 108 121 More recently, however, the CRVO study group recommended providing frequent follow up of at risk patients and application of laser when neovascularisation occurs122 because there was no benefit of prophylactic therapy over therapy when complications arise. The follow up recommended was at least monthly and perhaps more in the early stages of the condition.…”
Section: Treatment Of Crvomentioning
confidence: 90%
“…Prognosticating this complication has become important, since recent studies (Sedney, 1976;May et al, 1976;Laatikainen, 1977b) have reported that panretinal photocoagulation may be used to reverse or prevent iris neovascularisation after CRVO. It has been suggested, however, that treatment should be completed either early in the course of rubeosis, before extensive peripheral anterior synechiae are established, or prophylactically before clinical rubeosis is recognised.…”
mentioning
confidence: 99%